What Works and Does Not Work in a Self-Management Intervention for People With Chronic Pain? Qualitative Systematic Review and Meta-Synthesis. Issue 5 (16th April 2018) - Devan, Hemakumar; Hale, Leigh; Hempel, Dagmar; Saipe, Barbara; Perry, Meredith A
Abstract: Background: Self-management interventions fostering self-efficacy improve the well-being of people with chronic pain. Purpose: The purpose of this study was to synthesize the enablers (what works) and barriers (what does not) of incorporating self-management strategies for people in everyday life after completion of a pain self-management intervention. Data Sources: Major electronic databases (MEDLINE, AMED, PsycINFO, Cochrane Library, PubMed, CINAHL, Scopus, and Google Scholar) were searched from inception to July 2016. Study Selection: Study selection included qualitative and mixed-method studies that explored the perceptions of individuals with chronic pain after completion of a self–management intervention. Data Extraction: A thematic analysis approach was used to synthesize the review findings, and a Confidence in the Evidence from Reviews of Qualitative Research (CERQual) Approach was used to assess the level of confidence. Data Synthesis: Thirty-three studies with 512 participants were included. Enablers to self-management included self-discovery—the ability to distinguish self (ie, body, thoughts, and feelings) from pain; feeling empowered by incorporating self-management strategies into practice; and supportive ambience via collaborative relationships with clinicians and support from family and friends. Barriers to self-management included difficulty with sustaining motivation for pain self-management; distress experienced from ongoing pain, anxiety, and depression; and unsupportive relationships with clinicians, family, and friends. Limitations: This review only included interventions that involved at least 4 self–management skills; thus, informative studies may have been missed. The follow-up period varied from immediately after the intervention to 72 months following the intervention; therefore, it is uncertain which of the key enablers and barriers were most influential long term. Only articles published in the English language were included; studies conducted in low- and middle-income countries could not be located. Conclusions: The sustained effort to self-manage chronic pain could be exhausting, and motivation could wane over time following intervention. Providing intermittent support in the form of booster sessions and peer support groups may be important. Person-centered care via shared decision making and guided problem solving is essential to facilitating ongoing self-management.